Red Lesion Detection in Fundus Images – A Survey - Dr.S.Chidambaranathan , N.Laxmi Priyanka (International Journal of Advanced Science and Technology, 2020)
The detection of the disease in the eye known as Diabetic Retinopathy is done with the help of Fundus Photographs. These images are captured using a special type of camera called as Fundus camera which has three values namely Red, Green, and Blue respectively. Each value is quantised to 256 levels. Earlier detection of the disease plays a vital role for saving the vision of the affected person, if unnoticed might lead to blindness which is irreversible.This paper presents the analysis of various algorithms used to classify the detected lesions in the images.